Accelerated aging of Oenocarpus bacaba (ARECACEAE) diaspores - e Silva, Breno Marques da Silva [UNESP]; Sader, Rubens [UNESP]; Moro, Fabiola Vitti [UNESP]; de Oliveira, Camila; da Silveira, César Martoreli [UNESP] (FapUNIFESP (SciELO), 2009)
The evaluation of Oenocarpus bacaba diaspore physiological quality by means of the accelerated aging test was studied. The diaspores were submitted to temperatures of 41, 43, and 45 °C for 3, 6, 12, 24, 36, 48, and 72 h at a relative humidity of 100%. Two germination criteria were employed to evaluate the results:1. emission of the first 1 cm or longer sheath, and 2. normal seedling. The germination test was carried out with 6 replications of 20 diaspores at a temperature of 30 °C and a 12 h photoperiod. Based on preliminary results, four diaspore lots were submitted to 43 °C for 24, 48, and 72 h and the evaluation of germination was based on the emission of the first sheath. At 45 °C, germination percentage was severely reduced after 12 h. The use of the first sheath is suggested as germination criterion. The diaspore lots were more clearly separated when the accelerated aging test was conducted for 48 h at the temperature of 43 °C.
Envelhecimento acelerado em diásporos de Oenocarpus bacaba (ARECACEAE)
Keywords: Germination; Palmae; Viability; Vigor